Woman Representation in Poe’s To Helen - Fiola Kuhon (IdeBahasa, 2020)
Sir. Edgar Allan Poe was recognized for his gothic yet in depth writings. Every object he put in his works ended up as an interesting center of a literary study. Therefore, the aim of this research was to analyze the representation of a woman in Poe’s To Helen, the first version of the poem published in 1831. Meanwhile, to analyze the poem, an expressive approach and feminism approach were applied during this research. Hence, this research was a descriptive research where all the data were obtained and presented in words. Having analyzed this poem, it was discovered that in this poem, Poe depicted woman opposite to his major theme of beautiful victimized women. In this poem, the woman was represented as fair, caring, comforting and full of wisdom to the extent where a person found love and home in her.